EPT workshop - Nik Izyani, Nik Nordin (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
22-23 March 2012. A two-day workshop on EPT(English Placement Test) Specification and Item Construction has been conducted by the Modern Languages (ML) Department for ML associates specifically whom are working on the EPT project.